EFEKTIFITAS KINERJA PEGAWAI PADA KANTOR KECAMATAN UJUNG PADANG KABUPATEN SIMALUNGUN - Nur Laily Safitri; Julianan Nasution (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract This research was conducted to determine the effectiveness of employee performance at the Ujung Padang District Office, Simalungun Regency. This research belongs to the descriptive type of qualitative research. The unit of analysis in this study consisted of 6 people, namely the Head of Ujung Padang District, the Head of the Nagori Community Empowerment Section, the Head of the Economic and Development Section, one Ujung Padang District Staff and two people from the Ujung Padang District. Data collection techniques used are observation, interviews and documentation. The results showed that the effectiveness of employee performance at the Ujung Padang District Office, Simalungun Regency was effective. The assessments are quality, quantity, integrity, cooperation, time, service orientation, discipline, cost, commitment, and leadership.